Principles and Directions of Long-Term Stimulation of Innovation Activity in the Social Sphere - D. A. Serebryakov (Цифровая трансформация)
The article describes the main functions of socially oriented innovation in connection with technical innovations  – drivers of the third industrial revolution. Analysis of domestic and foreign innovative publications helped to formulate the basic principles of innovation in the social sphere. Directions of long-term stimulation of innovation activity in conditions of digital transformation have been developed. They are based on basic principles. It is also shown that the socio-economic development of the country should be based on qualitative population growth. Otherwise, the strategic importance of socio-economic policy is nulled and futuristic uncertainty comes. It is proposed to stimulate innovation in social sectors by increasing the innovative mentality of future generations of Belarusian people, improving the exchange of data in the system of information support of science, and by increasing the number of available sources of financing for innovations.